Development of Domain Ontology for a Semantic Online Forum - Hazalina Hashim; Shahrul Azman Mohd Noah (2015)
Ontology has the potential to structure domain knowledge and formally represent the knowledge in a more precise, explicit, consensusbased and meaningful manner. However, to our knowledge, none have made an effort to integrate forum discussion with subject module knowledge into ontologies to enhance learning of the subject taught. As such, it is the interest of this paper to reuse, classify, integrate and semantically organize both of this knowledge by means of ontological structure. Thus, detail of the ontology development process is presented consisting of two main phases: Namely knowledge acquisition (from both the subject module and forum discussion) and knowledge modeling. The resulting ontology was evaluated via the use of a prototype, a concept annotation task and questionnaires. Findings indicate that the proposed ontology model is sufficient to accommodate learning needs according to the assessment of experts. (Abstract by authors)